Analysis Of Application Minor Training Byte To Improve The Em-ployee Performance In The Food And Beverage Department At Anan-tara Uluwatu - Damayanti, Ni Komang Ayu Kristina; Darlina, Lien; Elistyawati, Ida Ayu (Jurnal Sains Terapan Pariwisata, 2022)
Purpose: This study discusses Minor Training Byte in improving the performance of employees of the food and beverage department of Hotel Anantara Uluwatu. The purpose of this study is to find out the influence between Minor Training Byte and the performance of food and beverage department employees at Hotel Anantara Uluwatu and to know how much Minor Training Byte ability affects the performance of employees of the food and beverage department at Hotel Anantara Uluwatu.Methods: The samples used were 60 members of the population. Data was collected through interview techniques, observations, questionnaires, literature studies, and documentation—data analysis using quantitative primary data analysis with simple linear regression analysis through the SPSS 20.0 program. Results and discussion: The results of this study show that Minor Training Byte has been done quite well, and all respondents agreed that Minor Training Byte was carried out well, with the most answers at 48%. However, there still needs to be some improvement by the management regarding the standards in conducting Minor Training Byte. There is an influence between the Minor Training Byte and the performance of employees of the Food and Beverage Department.Implication: This is evidenced by several assessments given by Food and Beverage Department employees (respondents) and test results that resulted in a calculated t value of 7,054 > t table of 2,0017. Most of the Minor Training Byte affect Employee Performance, as evidenced by the testing of a coefficient of determination of 0.642 or 62.4%. While the difference is 37.6%, it is the influence of other factors that do not participate in research and affect employee performance.